Digital Literacy Development Workshop in Developing Learning Tools for English Teachers in Wakatobi - Nur Hasanah Safei; Susanti Susanti; Jihan Fatikah Raihana (Jurnal Abdimas, 2024)
Realizing the importance of digital mastery in the era of the Industrial Revolution 4.0 in the world of education, the English Language Education study program held a digital literacy development workshop in compiling learning tools for English teachers in Wakatobi. The purpose of this workshop is to provide knowledge to teachers in integrating digital literacy in compiling learning tools. Through the Participation action research (PAR) approach, teachers and students will be more motivated to learn. The results of the implementation of the digital literacy development workshop which includes the use of Canva and ChatGPT for teachers in supporting classroom learning can be reflected in several positive aspects, as follows: First, it can be seen from the increase in teachers' understanding of the importance of digital literacy, how digital literacy plays a key role in supporting effective teaching and learning which encourages them to apply it in classroom learning. Second, it can be seen that teachers' graphic design skills have improved in creating interesting learning materials using the Canva platform. Teachers can create visual and attractive learning resources, increase student engagement and make it easier to understand the concepts being taught. The use of ChatGPT as a resource to support English learning can create a more dynamic learning experience. Teachers can use ChatGPT to provide writing exercises, provide quick feedback on student assignments, or even create simulated English conversations to improve students' speaking skills. This can make the class more interactive and facilitate adaptive learning. In terms of participation and engagement, this digital literacy development workshop can create a collaborative environment among teachers.